Worldwide scientific production on teleworking in Scopus in times of COVID-19 - Tito Betancur, Madona (2022)
Given the impact of COVID-19, teleworking has become an alternative work modality, so it is important to evaluate the scientific activity on the subject. Thus, the objective was to analyze the global scientific production on teleworking in times of COVID-19. Retrospective and descriptive study, whose unit of analysis was the publications on teleworking in journals indexed in the Scopus database between January 2020 and December 2021. The search was performed using the fields Article Title, Abstracts, Keywords, where 24 search terms were applied: teleworking, telecommuting, work from home, teleworking, telecommuting, work from home, online work, e-work, telecommuting, teletrabajo, trabado desde casa, trabajo online, e-trabajo, trabajo a distancia, teletrabalho, trabalho a partir de casa, trabalho em linha, trabalho electrónico, trabalho à distancia, and their relation with the term Covid-19. Likewise, 995 articles were found and 75.38% of them were original manuscripts. United States is the country with the largest scientific production with 21.21%. The Università degli Studi di Torino of Italy has published 10 papers and 80% of the articles on teleworking in times of COVID-19 have been published in quartile 1 and 2 journals. Teleworking in times of COVID-19 has been studied in several countries around the world as well as in different academic disciplines, which allows us to know progress on the subject, thereby generating policies and lines of research for the prevention of occupational hazards.